Analog integrated circuit design - Johns, David, 1958-; Martin, Kenneth W. (Kenneth William) 1952- (New York : John Wiley & Sons, 1997)
Offers a modern look at analog integrated circuit design. Covering everything from processing steps to models to high level circuit design issues, the authors make it a point to emphasize the "real-life" implications of this material for the circuit designer as a professional. This text presents a concise treatment of the wide array of knowledge required for integrated circuit design. Emphasis on the most important and fundamental principles in creating state-of-the-art analog circuits. Coverage includes contemporary topics such as dynamically matched current mirrors, digital error correction and interpolation, and folding D/D converters.
Partial table of contents: -- Integrated-Circuit Devices and Modelling. -- Processing and Layout. -- Basic Current Mirrors and Single-Stage Amplifiers. -- Noise Analysis and Modelling. -- Basic Opamp Design and Compensation. -- Advanced Current Mirrors and Opamps. -- Comparators. -- Switched-Capacitor Circuits. -- Nyquist-Rate D/A Converters. -- Oversampling Converters. -- Phase-Locked Loops. -- Index.
Includes bibliographical references and index.
1
Keywords: Analysis & Design of Analog Circuits; Linear integrated circuits -- Design and construction